Strategi Guru PAI dalam Mengatasi Kejenuhan Belajar Santri (Studi Kasus Marhalah Tsanawiyah TMI Putri AL-Amien Prenduan) - Ach. Nurholis Majid; Dewi Yanti (PT. Penerbit Tiga Mutiara, 2024)
Some children feel tired in learning and sleepy during teaching and learning activities. Class hours on Islamic religious education materials are also at time that cause children to feel sleepy. From this problem comes the saturation of learning that occurs in student. The aim of this research is to find out what the conditions for learning boredom are and what PAI teacher’s strategies are for overcoming learning boredom. The qualitative method is the method that will be used in this research, based on descriptive studies. This type of research in a case study. The research location is centered on Marhalah Tsanawiyah TMI Putri Al-Amien Prenduan. The technique for determining informants uses the purposive method. Data collection through observation, interviews, and documentation. Data analysis through data presentation, data reduction, and conclusions. The results show that the condition of learning boredom is characterized by 3 aspects, namely sleepiness, dizziness and chatting alone. The cause of learning boredom is due to busy activities and too much material. The time when learning boredom occurs during assignments and explanations of material. With learning boredom occurring, teachers use 4 strategies, namely the motivation method, educational punishment method, ice breaking method and integrative method.